Do foreign and domestic firms behave any different during economic slowdowns? - Varum, C.A. (2012)
The global crisis has called to further reflection on the role of multinationals in host economies during crisis. The evidence on this matter is scarce and no definite conclusions were achieved. Using panel data analysis, this paper examines the link between foreign ownership, firm employment and turnover growth over 20 years and during economic downturns in particular. We analyse the determinants of firm employment and turnover growth and investigate whether there are significant differences in both variables among domestic and foreign firms when controlling for firm and industry specificities. Additionally we assess if the foreignness effect alters during economic downturns. After controlling for several firm and industry characteristics, we find no significant differences between domestic and foreign firms in what concerns employment growth. However, our results suggest that foreign ownership may affect positively firms' sales turnover growth during recessions.